Gastos do governo federal na proteç\~ao da biodiversidade e das paisagens (2001-2022): As despesas tímidas do país que abriga a maior biodiversidade do planeta - Jo\~ao Paulo Viana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The federal government's spending on the protection of biodiversity and landscapes between 2001 and 2022 was analyzed in detail by applying the Classification of Environmental Activities (CEA) to federal budgetary actions. To this end, the budgetary actions were classified into three adapted CEA subclasses and, additionally, a classification consisting of twelve thematic subclasses was developed, to express the variety of the federal government's budgetary actions and activities aimed at protecting biodiversity and landscapes. The three most important themes identified were: fighting forest fires and deforestation, protection of conservation units and protection of Indigenous lands. Spending by Brazil's central/federal government on the protection of biodiversity and landscapes proved to be relatively modest when compared to Chile and Costa Rica, whereas is equivalent to spending in Peru. Considering that Brazil is the country with the greatest biodiversity on the planet, this is a strong indication that this agenda is underfunded. In other words, the governments that succeeded each other in charge of the country over the last twenty-two years gave low budgetary priority to this issue. Additionally, the comparison of research estimates with those of the Biodiversity Finance Initiative (Biofin) and the application of the Classification of Government Functions (Cofog) to the General Budget of the Union (Orçamento-Geral da Uni\~ao - OGU) revealed important differences, especially in the case of the Biofin Initiative, a consequence of variety of types of environmental themes that may have a positive impact on biodiversity, according to the methodology developed by UNDP. The estimates produced by the application of CEA and Cofog proved to be compatible, as long as adjustments were applied, and methodological improvements were proposed in the application of both classifications to the OGU. Experiences developed by Brazil to overcome underfunding in the protection of biodiversity and landscapes have presented ambiguous results: the Bolsa Verde Program was canceled by the Ministry of the Environment in 2017, after seven years of implementation, due to budgetary restrictions; while the Amazon Fund, financed mainly by international donations, was the target of interference during the Bolsonaro period that resulted in its interruption. These two initiatives were resumed in 2023 with the inauguration of the Lula 3 government. What happened in these two cases demonstrates the fragility to which certain types of initiatives on the environmental agenda are exposed, dependent on budgetary restrictions or the political bias of successive governments. From the point of view of the Executive Branch, the current moment tends to be favorable to the environment agenda. Otherwise, and from the point of view of the budgetary space, recent changes in the budgetary governance process may have negative impacts. Considering the known limitation of resources for the environmental agenda and the growing influence of the Legislative Branch over the budgetary process, it is possible that it will become increasingly difficult to allocate resources to themes considered priorities by operators of environmental policies. Based on this scenario, it will not be surprising if the shyness of federal spending on protecting biodiversity and landscapes becomes more evident.
Keywords: Q00; 330; Brazil; biodiversity; federal government; environmental expenditures; environmental statistics; public budget; Classification of Environmental Activities; Biofin; Cofog